Pengaruh Burnout, Work Life Balance, dan Employee Engagement Terhadap Loyalitas Pegawai Sekretariat DPRD Kabupaten Karanganyar - Rizka Azizah Fatmasari; Nanda Sholeha Tuhzzarrah; Eva Mustika (Jurnal of Management and Social Sciences, 2026)
To optimize public sector organizational efficiency, this study examines how employee loyalty at the Karanganyar Regency DPRD Secretariat is influenced by job burnout, work-life balance, and employee engagement. Employing a quantitative approach with total sampling (saturation sampling), all 41 active staff members served as respondents through a digital questionnaire utilizing a five-point Likert scale. Data analysis applied multiple linear regression via SPSS, undergoing instrument testing (Pearson validity and Cronbach's alpha reliability) alongside classical assumption tests. Collectively, the F-test results demonstrate that these three aspects contribute significantly to job loyalty. Nevertheless, partial T-test analysis reveals that physical exhaustion shows no meaningful dependency, yielding a calculated t-value of −1.059 and a significance level of 0.296. A similar pattern occurs in work-life balance, which generates a t-score of −0.571 (sig. = 0.571). Conversely, employee engagement proves to be the most dominant determinant with a strong positive effect, where the t-value reaches 6.031, p = 0.000, and a standardized beta coefficient of 0.718. This model yields an Adjusted R Square value of 0.577. This indicates that 57.7% of loyalty variability is explained by the independent variables, while the remaining portion is influenced by unobserved external factors. Consequently, strengthening employee engagement serves as the primary tactical instrument for maintaining staff loyalty within the institution